Do You See What I See? The Consequences of Objectification in Work Settings for Experiencers and Third Party Predictors. Issue 1 (25th May 2016) - Gervais, Sarah J.; Wiener, Richard L.; Allen, Jill; Farnum, Katlyn S.; Kimble, Katherine
Abstract : Sexual objectification is a significant problem that permeates all areas of women's lives including the workplace. This research examines the impact of sexual objectification on women in work settings by integrating objectification, sexual harassment, and affective forecasting theories. We used a laboratory analogue that included undergraduate women who actually experienced objectification during a work interview (i.e., experiencers) and third‐party predictors (including female and male undergraduates as well as female and male community workers) who anticipated the effects of objectification (i.e., predictors). We measured actual and anticipated emotions, performance, and sexual harassment following objectification. We found that both mild and severe objectification caused weaker positive affect, stronger negative affect, worse work performance, and higher sexual harassment judgments, but these effects were primarily driven by predictors anticipating worse outcomes following objectification compared to what experiencers actually reported. We also found that experiencers' responses to objectification were moderated by benevolent sexism with women lower in benevolent sexism responding more similarly to predictors relative to women higher in benevolent sexism. Both experiencers and predictors evaluated interviewers who engaged in objectification equally negatively. Finally, we explored differences between predictors who were female and male undergraduate students versus community workers and found that these parties anticipated different consequences, depending on worker status and gender. Implications for sexual objectification, sexual harassment, and affective forecasting theories as well as practical implications for policy and law are discussed.